Chronic Pain and DepressionAmong Primary Care Patients Treated with Buprenorphine - Stein, Michael D. (J Gen Intern Med, 2015)
BACKGROUND: Pain and depression are each prevalent among opioid dependent patients receiving maintenance buprenorphine, but their interaction has not been studied in primary care patients. OBJECTIVE: We set out to examine the relationship between chronic pain, depression, and ongoing substance use, among persons maintained on buprenorphine in primary care settings. DESIGN: Between September 2012 and December 2013, we interviewed buprenorphine patients at three practice sites. PARTICIPANTS: Opioid dependent persons at two private internal medicine offices and a federally qualified health center participated in the study. MAIN MEASURES: Pain was measured in terms of chronicity, with chronic pain being defined as pain lasting at least 6 months; and in terms of severity, as measured by self-reported pain in the past week, measured on a 0–100 scale. We defined mild chronic pain as pain severity between 0 and 39 and lasting at least 6 months, and moderate/severe chronic pain as severity ≥ 40 and lasting at least 6 months. To assess depression, we used the Center for Epidemiologic Studies Depression (CESD) ten-item symptom scale and the two-item Patient Health Questionnaire (PHQ-2). KEY RESULTS: Among 328 participants, 169 reported no chronic pain, 56 reported mild chronic pain, and 103 reported moderate/severe chronic pain. Participants with moderate/severe chronic pain commonly used non-opioid pain medications (56.3 %) and antidepressants (44.7 %), yet also used marijuana, alcohol, or cocaine (40.8 %) to help relieve pain. Mean CESD scores were 7.1 (±6.8), 8.3 (±6.0), and 13.6 (±7.6) in the no chronic, mild, and moderate/severe pain groups, respectively. Controlling for covariates, higher CESD scores were associated with a higher likelihood of moderate/severe chronic pain relative to both no chronic pain (OR = 1.09, p < 0.001) and mild chronic pain (OR = 1.06, p = 0.04). CONCLUSION: Many buprenorphine patients are receiving over-the-counter or prescribed pain medications, as well as antidepressants, and yet continue to have significant and disabling pain and depressive symptoms. There is a clear need to address the pain–depression nexus in novel ways.